2011
DOI: 10.1248/bpb.34.354
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Hippocampal Atrophy in Chronic Fatigue Mice by Enhancing Neurogenesis and Inhibiting Apoptosis of Granular Cells

Abstract: Chronic fatigue is reported in more than 20% of patients examined in primary care, and this common problem affects the quality of life and work productivity.1) A large part of the chronic fatigue population meets the diagnostic criteria for chronic fatigue syndrome (CFS), which is defined by unexplained physical or mental fatigue of at least 6-month duration and a combination of nonspecific symptoms.2) Several CFS symptoms including impaired concentration, attention, and memory as well as headache suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 46 publications
3
37
0
1
Order By: Relevance
“…insulin sensitivity) (32), and counteract disease processes in animal models of cancers (38), cardiovascular disease (39), and some neurodegenerative conditions (40). It was also recently reported that resveratrol can promote the survival of hippocampal NPCs in an animal model of neuroinflammation (41). While resveratrol may protect neurons against oxidative and inflammatory stress, our findings suggest that in healthy mice NPCs are adversely affected by resveratrol.…”
Section: Discussionsupporting
confidence: 53%
“…insulin sensitivity) (32), and counteract disease processes in animal models of cancers (38), cardiovascular disease (39), and some neurodegenerative conditions (40). It was also recently reported that resveratrol can promote the survival of hippocampal NPCs in an animal model of neuroinflammation (41). While resveratrol may protect neurons against oxidative and inflammatory stress, our findings suggest that in healthy mice NPCs are adversely affected by resveratrol.…”
Section: Discussionsupporting
confidence: 53%
“…The expression of hippocampal brain-derived neurotrophic factor (BDNF) mRNA decreases under conditions of hippocampal atrophy (16). In addition, there is a positive association between the quantity of BDNF in the serum and cerebrocortex (17).…”
Section: Locomotor Activity Laboratory Findings For the Open Field Tementioning
confidence: 99%
“…Resveratrol has also been shown to reduce neuronal apoptosis by up-regulating the expression of Bcl-2 and down-regulating the expression of Bax in the hippocampus after focal cerebral ischemia in rats [12]. Moreover, resveratrol enhanced hippocampal neurogenesis and improved hippocampal atrophy in chronic fatigue mice and prenatally stressed rats [13,14]. However, the effect of resveratrol on neurogenesis after cerebral ischemic damage is largely unknown.…”
Section: Introductionmentioning
confidence: 99%